The poetic rite of rebirth in Sylvia Plath's “Lady Lazarus“ - Novkinić, Sandra (Anafora, 2022)
The aim of this paper is to demonstrate the inviolability of „female creativity” in the works of Sylvia Plath through the symbolism of death and rebirth. „Lady Lazarus” reflects Plath’s recognition that the struggle between death and rebirth must direct every aspect of poetic structure. The woman in the poem is at the same time a victim and tormentor. She is a female Lazarus who died because of great suffering that the poet equates with the suffering of the Jews who were tortured during World War II. She is a victim of male cruelty, but also a new woman who rises from the flames. Using the myth of the resurrection of the Phoenix, Sylvia Plath shows a woman who stands up against all the men who restrain her. The allusions in the poem to the biblical, historical, political and personal take the reader into the center of a personality (of a woman).